Fundamentals of Entrepreneurship (ENT300) : Wisi Snacks / Muhammad Syazwi Mohd Yusri - Mohd Yusri, Muhammad Syazwi (2020)
A snack is a small service of food and generally eaten between meals. Snacks come in a variety of forms including packaged snack foods and other processed foods, as well as items made from fresh ingredients at home. Snack foods are typically designed to be portable, quick, and satisfying. Processed snack foods, as one form of convenience food, are designed to be less perishable, more durable, and more portable than prepared foods. They often contain substantial amounts of sweeteners, preservatives, and appealing ingredients such as chocolate, and specially - designed flavours such as flavoured potato chips.